Cytotoxic effects of hard-setting cements applied on the odontoblast cell line MDPC-23 - Melo de Mendonça, Adriano Augusto; Chaves Souza, Pedro Paulo; Hebling, Josimeri; de Souza Costa, Carlos Alberto (Elsevier, 2007)
Objective: The present study evaluated the cytotoxic effects of hard setting applied on the odontoblastlike cells MDPC-23. Study design: Eighty round-shaped samples were prepared with the following experimental materials: calcium hydroxide, Vitrebond, RelyX Luting, and RelyX Unicem. The samples were placed in serum-free culture medium and incubated for 24 hours or 7 days at 37°C with 5% CO 2 and 95% air. The odontoblast cells were plated in the wells and incubated for 72 hours. After this period, the complete culture medium was replaced by the extracts obtained from every sample, and the methyltetrazolium assay was carried out to evaluate the cell metabolism. Results: For the 24-hour period, the experimental materials calcium hydroxide, Vitrebond, RelyX Luting, and RelyX Unicem decreased the cell metabolic activity by 91.52%, 81.14%, 78.17%, and 2.64%, respectively. For the 7-day period, calcium hydroxide, Vitrebond, RelyX Luting, and RelyX Unicem decreased the metabolic activity of the MDPC-23 cells by 91.13%, 87.27%, 79.04%, and 10.51%, respectively. Conclusion: RelyX Unicem presented the lowest cytopathic effects to the cultured odontoblast cell line. © 2007 Mosby, Inc. All rights reserved.
Keywords: glass ionomer; resin cement; root canal filling material; cell line; drug effect; human; odontoblast; Cell Line, Transformed; Glass Ionomer Cements; Humans; Odontoblasts; Resin Cements; Root Canal Filling Materials